Teori Sinyal Dalam Anomali Window Dressing 2022 Dan Penurunan Risiko Kredit Macet Pada Subsektor Perbankan: Studi Kasus Isu Resesi 2023 - Isnin Yulia Alfiani Rochman; Sari Andayani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aimed to test signalling theory in the phenomenon of window dressing anomaly, risk reduction of bad loans, and the 2023 recession issue. Macroeconomic variables were used as independent variables which were reflected by GDP, inflation, and BI interest rates; banking sub-sector share prices as the dependent variable; and the ratio of Non-Performing Loans as a mediating variable. The population in this study were banking sub-sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. The research sample consisted of 12 companies obtained using a purposive sampling technique. Data analysis techniques and hypothesis testing using path analysis with the help of SPSS 25. The results of the study showed that the signal theory was not proven to always be appropriate in terms of stock price fluctuations and its relation to the phenomenon of the 2023 recession issue, as evidenced by the absence of a significant relationship between the independent and dependent variables. The implication of this research is for long-term investors to not to rush into making investment decisions due to concerns over issues that are currently being discussed, the truth of which cannot be ascertained.